Effect of pH and Monomer Dosing Rate in the Anionic Polymerization of Ethyl Cyanoacrylate in Semicontinuous Operation - Hened Saade; Suleidi Torres; Cynthia Barrera; Julieta Sánchez; Yolanda Garza; Raúl G. López (International Journal of Polymer Science)
Nanoparticles of poly(ethyl cyanoacrylate) with more than 10% solids content were prepared by semicontinuous heterophase polymerization at monomer-starved conditions varying the initial pH in the interval of 1–1.75 and at two monomer dosing rates. Measurements by scanning-transmission electron microscopy allowed us to identify an inverse dependence of particle size on pH. Furthermore, all the polymerizations conducted at the slower monomer dosing rate rendered two particle populations, with the larger one formed from the aggregation of a fraction of the smaller particles. It was believed that the so slow addition of the monomer caused the formation of very small but instable particles, thereby a fraction of which aggregated to reduce the total interface particles-aqueous phase, increasing the latex stability. An increase in the monomer dosing rate led to larger and more stable particles in such way that only one population of nanoparticles with around 40 nm in average diameter was obtained.